PERILAKU MENYONTEK SISWA DITINJAU DARI JENIS KELAMIN - Musslifah, Anniez Rachmawati (Universitas Sahid Surakarta, 2015)
ABSTRACTCheating behavior is one of the educational phenomenon that we often encounter accompany the learning process. There are various factors that influence the behavior of cheating, one of the factors that influence the behavior of such cheating is sex. This study aims to analyze the extent to which gender affects the behavior of cheating on the students.Population in this research is the students of SMAN 1 Widodaren with a sample size of 70 people. Samples were taken at random cluster sampling technique. The data collection method using a scale behavior of cheating which is then analyzed by Annava one lane.The analysis showed that there was no significant difference in terms of cheating behavior in terms of sex differences with F value of 2.813 with p = 0.094 (p> 0.05). These results indicate that gender does not affect the behavior of cheating on the students.Keywords: sex, cheating behavio